2003
DOI: 10.1289/ehp.5813
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of protein allergenicity on the basis of immune reactivity: animal models.

Abstract: Because of the public concern surrounding the issue of the safety of genetically modified organisms, it is critical to have appropriate methodologies to aid investigators in identifying potential hazards associated with consumption of foods produced with these materials. A recent panel of experts convened by the Food and Agriculture Organization and World Health Organization suggested there is scientific evidence that using data from animal studies will contribute important information regarding the allergenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…In the present experiments, high levels of specific IgE and IgG1 were obtained using PCA, which is one of the most important in vivo models of anaphylaxis in a local allergic reaction [26][27][28]. A recent study by Christensen et al [29] has shown that soybean protein could induce high levels of glycinin or b-conglycinin-specific serum antibody responses in BALB/c mice immunized with soybean protein by oral administration.…”
Section: Discussionmentioning
confidence: 57%
“…In the present experiments, high levels of specific IgE and IgG1 were obtained using PCA, which is one of the most important in vivo models of anaphylaxis in a local allergic reaction [26][27][28]. A recent study by Christensen et al [29] has shown that soybean protein could induce high levels of glycinin or b-conglycinin-specific serum antibody responses in BALB/c mice immunized with soybean protein by oral administration.…”
Section: Discussionmentioning
confidence: 57%
“…This is especially the case for sub-classes of IgG that are regulated in a manner similar to IgE (as surrogates for IgE). In the rat, IgG 2a antibody is subject to similar cytokine regulation as IgE (Saoudi et al, 1993;Gracie and Bradley, 1996;Kimber et al, 2003). Oral exposure of BN rats to OVA led to stimulated IgG and IgG 2a antibody responses that were generally expressed as higher titers relative to those in Wistar rat counterparts, with the exception of IgG on day 14.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown that glycinin contributes to a series of allergic reactions, damage to intestinal morphology, disorder of immune function, growth depression and diarrhea in human infants [11] and piglets [12][13][14][15], the underlying mechanisms causing these symptoms are largely unknown. Because the piglet is widely used as an animal model for studying sensitization of infants to soy proteins [13][14][15][16][17][18], it was used in the present study to define mechanisms whereby glycinin increases hypersensitivity in response to consumption of soybean products.…”
Section: Introductionmentioning
confidence: 99%